Enzyme‐Modified Particles for Selective Biocatalytic Hydrogenation by Hydrogen‐Driven NADH Recycling. Issue 21 (28th October 2015) - Reeve, Holly A.; Lauterbach, Lars; Lenz, Oliver; Vincent, Kylie A.
Abstract: We describe a new approach to selective H2 ‐driven hydrogenation that exploits a sequence of enzymes immobilised on carbon particles. We used a catalyst system that comprised alcohol dehydrogenase, hydrogenase and an NAD + reductase on carbon black to demonstrate a greater than 98 % conversion of acetophenone to phenylethanol. Oxidation of H2 by the hydrogenase provides electrons through the carbon for NAD + reduction to recycle the NADH cofactor required by the alcohol dehydrogenase. This biocatalytic system operates over the pH range 6–8 or in un‐buffered water, and can function at low concentrations of the cofactor (10 μm NAD + ) and at H2 partial pressures below 1 bar. Total turnover numbers >130 000 during acetophenone reduction indicate high enzyme stability, and the immobilised enzymes can be recovered by a simple centrifugation step and re‐used several times. This offers a route to convenient, atom‐efficient operation of NADH‐dependent oxidoreductases for selective hydrogenation catalysis. Abstract : Heterogeneous hydrogenation : A system of enzyme‐modified particles allows H2 ‐driven NADH supply for NADH‐dependent biocatalyzed hydrogenations.